Seasonal prevalence of gastrointestinal parasitic infections in goats in a commercial farm Kuantan, Malaysia - Raja Nur Rahifah Inani, Raja Abdul Rahman; Mat Yusof, Afzan (Asian Journal of Agriculture and Biology, 2018)
Gastrointestinal parasitic infection is a major concern to livestock sector as it causes severe diseases and death to the goats. This study was designed to measure the occurrence of gastrointestinal parasitic infections in goats and its association with the seasonal variations in a commercial farm located in Kuantan, Malaysia. A total of 480 faecal samples were collected randomly from 40 goats in 12 months. All samples were processed under faecal flotation technique for morphology and size of the egg/oocyst of parasites and McMaster modified technique for the OPG/EPG of parasites. The obtained data were analysed by using SPSS software under independent t-test and chi-square test. Out of 480 faecal samples, 429 samples were positive and give the overall prevalence 89.4%. The infection rate was significantly higher in a dry climate (92.1%) than wet climate (85.5%). The mean egg counts of Strongyles, Strongyloides, and Enterobius were significantly higher in a dry climate than wet climate (P<0.005). Meanwhile, the mean egg or oocyst counts of Trichuris, Moniezia and Eimeria were higher in wet climate than dry climate, but the results were not significant. The findings from the present study suggested that appropriate preventive measures such as maintaining cleanliness and provide appropriate anthelminthic to goats need to be applied to the goats, farms and farm workers to prevent the widespread of infections to goats and humans.